Impact of Pyrolyzed and Unpyrolyzed Animal Manures on Soil Properties, Carbon Sequestration, and Clover Productivity in Andisol - Muñoz, Cristina (2024)
The use of organic waste in agricultural soil can enhance crop yields, improve waste management, and boost soil carbon (C) sequestration. However, more field data are required to fully understand the impacts of pyrolyzed and unpyrolyzed animal manures. The objectives of this study were (i) to analyze the impact of two pyrolyzed and unpyrolyzed manures on soil properties, soil C storage, and clover productivity and (ii) to examine the biochar’s movement through the soil profile. Poultry litter (PL), dairy manure (DM), poultry litter biochar (PLBC), and dairy manure biochar (DBC) were applied at rates of 8 t ha−1 in a field experiment with red clover (Trifolium pratense L. var. Quiñequeli) in an Andisol. We monitored changes in soil chemical properties, foliar properties, and crop yield after three clover cuttings. To examine the movement of biochars through the soil profile, we set up a lab experiment where field conditions were simulated. PLBC, DBC, and PL increased soil pH by 0.5 (6.44), 0.28 (6.22), and 0.25 (6.19) units, respectively. Soil available P increased in both pyrolyzed and unpyrolyzed PL treatments (by 8.53 mg P kg−1 , on average). Clover yields only increased in treatments with amendments that provided more available P and increased the pH. The addition of DBC increased soil total C (30.3%). Both biochars added to the soil surface exhibited little movement through the soil profile (2 to 4 cm). In this study, the pyrolysis of manures emerged as an option for reducing waste volume from the farming industry. Manure biochars proved useful at low rates for enhancing crop yields (PLBC) and storing C in the soil (DBC).